Effectiveness of an online mental health strengthening module to build resilience and overcome stress for transitional aged medical students - Kaligis Fransiska; Ismail Raden Irawati; Wiguna Tjhin; Prasetyo Sabarinah; Gunardi Hartono; Indriatmi Wresti; Pasaribu Merci Monica; Pandia Veranita; Minayati Kusuma; Magdalena Clarissa Cita; Nurraga Garda Widhi; Pramatirta Billy; et al. (Frontiers, 2025)
Introduction: Transitional-aged youths (17-to-24-years-old) are prone to mental-health problems. Students in higher education, especially medical students, are more exposed to stressors and thus need training to increase resilience. However, there have been limited mental-health strengthening modules specifically developed for medical students of transitional age, and none in Indonesia. This study intends to test the effectiveness of an online mental-health strengthening module in altering resilience.
Methods: A pragmatic randomized trial with repeated measurements was employed to evaluate biopsychosocial outcomes of resilience. The intervention module was delivered in 4 weeks to 105 eligible students. Participants were divided into intervention group (n = 52) and control group (n = 53). Outcomes were measured in the 4th, 8th, and 12th weeks. Primary outcome was resilience level as measured by Connor-Davidson Resilience Scale (CD-RISC). Perceived Stress Scale (PSS), Depression Anxiety Stress Scale (DASS) were utilized to measure stress, depression and anxiety. Knowledge and attitude toward mental-health were also measured through validated questionnaires. Stress levels of participants were measured biologically by measuring salivary cortisol and alpha-amylase levels at the baseline and 12th-week.
Results: Compared to the control group, there were no significant difference in resilience score of the intervention group compared to control group [F(1, 103) = 2.243, P = .137]; however, there was a significant main effect of time [F(3, 309) = 18.191, P < .001] and interaction effect between intervention and time in resilience score [F(3, 309) = 5.056, P = .002]. Additionally, compared to the control group, there were significant increases in knowledge [F(1, 103) = 66.805, P < .001], attitudes and behavior towards mental-health [F(1, 103) = 5.191, P = .025], and a significant decrease in stress perception score [F(1, 103) = 27.567, P < .001]. The mean salivary delta cortisol during pre-test and post-test at week 12 in the intervention group showed significant difference (P < .001). However, there was no significant difference in the mean delta salivary alpha-amylase between pre-test and post-test at week 12, both in the intervention and control groups.
Conclusion: The mental-health strengthening module was accepted and applicable to first-year medical students and was found to be effective in increasing resilience from various biopsychosocial aspects. It is also advisable to have similar modules throughout the medical school to maintain sustainability.